Degradation of SOFCs by Various Impurities: Impedance Spectroscopy and Microstructural Analysis. (30th May 2017) - Kikuchi, Yuhdai; Matsuda, Junko; Tachikawa, Yuya; Shiratori, Yusuke; Taniguchi, Shunsuke; Sasaki, Kazunari
Abstract : SOFC can use various kinds of fuels besides hydrogen, including coal gas, digestion gas, and biogas. On the other hand, it is known that practical fuel such as coal gas and digestion gas contain various fuel impurities such as phosphorus, siloxane, and sulfur, affecting fuel cell performance. Here, a case study is made to understand the impurity poisoning phenomena through both electrochemical and microstructural analysis to analyze poisoning mechanisms especially using the DRT (Distribution of Relaxation Times) analysis.